2022
DOI: 10.1111/bju.15669
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and safety of radical prostatectomy for oligo‐metastatic prostate cancer: the Testing Radical prostatectomy in men with prostate cancer and oligo‐Metastases to the bone (TRoMbone) trial

Abstract: Objectives To test the feasibility of randomisation to radical prostatectomy (RP) plus pelvic lymphadenectomy in addition to standard‐of‐care (SOC) systemic therapy in men with newly diagnosed oligo‐metastatic prostate cancer. Patients and Methods A prospective, randomised, non‐blinded, feasibility clinical trial with an embedded QuinteT Recruitment Intervention (QRI) to optimise recruitment was conducted in nine nationwide tertiary care centres undertaking high‐volume robotic surgery. We aimed to randomise 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 30 publications
1
18
0
Order By: Relevance
“… 56 Overall, perioperative complication rates for CRP ranged between 12% and 34%. 60 , 67 , 68 , 72 Comparing CRP to RPx in nonmetastatic PCa in a population-based cohort, CRP was associated with slightly higher overall complication rates (14.9% versus 12.3%), but the inherent limitations of population-based databases were a bias. 73 In a retrospective study that assessed perioperative outcomes in patients undergoing robot-assisted CRP for omPCa, 5.3% of the men experienced Clavien–Dindo classification (CDC) grade III complications but no grade IV or grade V complications.…”
Section: Treatment Of the Primarymentioning
confidence: 99%
See 3 more Smart Citations
“… 56 Overall, perioperative complication rates for CRP ranged between 12% and 34%. 60 , 67 , 68 , 72 Comparing CRP to RPx in nonmetastatic PCa in a population-based cohort, CRP was associated with slightly higher overall complication rates (14.9% versus 12.3%), but the inherent limitations of population-based databases were a bias. 73 In a retrospective study that assessed perioperative outcomes in patients undergoing robot-assisted CRP for omPCa, 5.3% of the men experienced Clavien–Dindo classification (CDC) grade III complications but no grade IV or grade V complications.…”
Section: Treatment Of the Primarymentioning
confidence: 99%
“…Recently, the TRoMbone trial successfully randomized 51 patients with newly diagnosed omPCa to CRP plus SOC versus SOC (ADT ± docetaxel) alone. 72 The study showed that it is feasible to randomize patients with de novo omHSPC to a surgical intervention providing the groundwork for larger trials. 72 In addition, there was no difference in the QOL between the two groups confirming the results of retrospective studies that did not find a significant difference in QOL outcomes in men undergoing CRP compared to men with localized PCa at the time of surgery.…”
Section: Treatment Of the Primarymentioning
confidence: 99%
See 2 more Smart Citations
“…As with many critical clinical trials that have taken place before the widespread use of emerging PET radiotracers for prostate cancer staging, these definitions rely primarily on findings as seen on CT, MRI, and 99m Tc-methyl diphosphonate (MDP) skeletal scintigraphy. Through these trials (and others, including the STAMPEDE and HORRAD trials), many important conclusions were made regarding the prognosis and treatment of patients with oligometastatic prostate cancer at the time, often utilizing a combination of systemic therapy, targeted radiotherapy, and/or surgical resection with varying definitions of oligometastatic disease [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. However, as the utilization of PET-based molecular imaging for prostate cancer staging has increased, there is increasing uncertainty on how to apply the conclusions of these important clinical trials, performed in the past relying on conventional staging imaging modalities to disease detected through higher sensitivity, more novel PET imaging.…”
Section: Historical Definition Of Oligometastatic Disease and Relevan...mentioning
confidence: 99%